2018
DOI: 10.30543/7-2(2018)-7
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media as One of Learning Tool: Facebook Enhances Learning Practices among Higher Learning Students in Malaysia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…This finding aligns with results from numerous studies in this field, indicating that QR codes allow for autonomy and directed learning, supporting student-centred learning (Jacobs & Renandya, 2016;Bremner et al, 2022). In line with findings from Shahril et al, (2019), who stated that QR codes offer convenience, fostering positive student behaviours and boosting their involvement in classroom activities. Additionally, these codes serve as a catalyst for educators to incorporate technology-driven approaches into the educational process.…”
Section: Quick Response Codes In Promoting Student-centred Learningsupporting
confidence: 90%
“…This finding aligns with results from numerous studies in this field, indicating that QR codes allow for autonomy and directed learning, supporting student-centred learning (Jacobs & Renandya, 2016;Bremner et al, 2022). In line with findings from Shahril et al, (2019), who stated that QR codes offer convenience, fostering positive student behaviours and boosting their involvement in classroom activities. Additionally, these codes serve as a catalyst for educators to incorporate technology-driven approaches into the educational process.…”
Section: Quick Response Codes In Promoting Student-centred Learningsupporting
confidence: 90%
“…Some scholars (Ramsden, 2008;Googova & Koceska, 2014;Chee & Tan, 2021) argue that QR codes are beneficial to raise standards in education, while others (Bakla, 2018;Alzubi, 2019;Ding et al, 2019) elucidate that they pose some risks for educators and learners. To name a few, Shahril et al (2019) postulate that QR codes serve as an interactive tool to form a communication bridge between the teacher and the students. Additionally, Ali et al ( 2017) assert that QR codes can function to provide links, videos and illustrations, so students' learning can be enhanced dramatically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The students admitted that Facebook gave them a chance to practise English. Shahril et al (2018) also carried out a study exploring Facebook as a learning tool and found that Facebook increases students' enthusiasm and motivation in learning. The study also strongly recommended that educators at tertiary institutions entirely use social media as an educational tool to enhance and improve students' learning experiences (Shahril et al, 2018).…”
Section: Perceptions Of Facebook Among Learnersmentioning
confidence: 99%